Agentic practice and privileging orientations among privately educated young women. Issue 4 (14th August 2014) - Maxwell, Claire; Aggleton, Peter
Abstract This paper examines factors driving the agentic practices of young women who are privately educated. The analysis informing this paper comes from a three‐year study, in which 91 young women aged 15–19 years were interviewed. Four private schools in one area of middle England participated in the research, and over half of the young women were re‐interviewed 12–18 months later. Our starting point is the degree to which particular orientations within families are aligned to those being promoted within the various private schools in our study. The affective experiences of alignment but also of disorientation within and between the family and the school, drive significant forms of internal conversation (Archer, 2003). In this paper we examine two kinds of internal conversations found within our study – one that is assured and optimistic, and another, which is more fractured. These different internal conversations lead to the emergence of differing projects of the self, expressed through practices that by their very nature of being committed to self‐directed progress can be understood as being agentic. The consequences of these different projects of the self suggest that the reproduction of class privilege cannot be taken for granted – but is always provisional and contested, even among those who are privately educated.